Anterior Skull Base Reconstruction Using a Vascularized Pericranial Flap: A Promising Alternative in Sinonasal Malignancies - Joseph, Jeena; Govind, Arun; Vediappan, Rajan Sundaresan; Thomas, Regi; Jonathan, Gandham Edmond; Raju, Krishnaprabhu (Journal of Neurological Surgery Part B: Skull Base, 2024)
As the scope of endoscopic techniques continues to evolve in the treatment of advanced sinonasal malignancies, the primary challenge is the reconstruction of the resulting anterior skull base dural defect.This study aimed to assess the efficacy of vascularized pericranial flap reconstruction in addressing anterior skull base defects in sinonasal malignancies, particularly when alternative reconstructive methods, such as nasoseptal flaps, are not viable.We conducted a retrospective review of nine patients who underwent endoscopic resection of sinonasal malignancy followed by vascularized pericranial flap. Our analysis aimed to evaluate the surgical methods utilized, identify any complications that occurred, and assess the postoperative results of the patients.Excluding the singular instance of tension pneumocephalus that emerged during the immediate postoperative period, necessitating surgical intervention, our clinical experience was devoid of any complications, with a median follow-up duration of 18 months. It is worth noting that no cases of cerebrospinal fluid leaks or meningitis were reported. Moreover, the follow-up check endoscopy verified the successful integration of the flap and its efficacious coverage of the resection site.This study underscores the benefits of using vascularized pericranial flaps as an alternative solution for anterior skull base reconstruction in sinonasal malignancies. The availability of the pericranial flap in the local region, along with its robust blood supply, and the positive outcomes observed in this preliminary series collectively indicate its potential as an integral component of multi-layered reconstruction techniques for addressing anterior skull base defects.
Keywords: anterior skull base; sinonasal malignancies; pericranial flap